Challenges encountered: A Qualitative analysis of professionals’ lived experiences in the field of autism - Bobadilla, Tony; Hebert, Elizabeth Baltus; Espinoza, Janet (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
Autism Spectrum Disorder (ASD) significantly impacts American families, requiring substantial support from professionals in the field. This qualitative study explores the experiences of nine professionals in the ASD field using a phenomenological framework. Four main themes emerged from the analysis: 1) Service Delivery Constraints, 2) Knowledge Limitations, 3) Professional Adaptation, and 4) Future Directions. These findings illuminate the unique challenges professionals face in service delivery and their roles within the autism field. The study provides practical and scholarly insights based on real-life experiences, benefiting professionals, scholars, and families with children with autism.